Faktor Protektif Perundungan Siber pada Siswa Sekolah Menengah Atas di Kota Bandung - Alifah Nur Annisa Jatnika; Ihsana Sabriani Borualogo (UNISBA Press, 2022)
Abstract. The purpose of this research is to investigate the protective factors of cyber-bullying on high school students in Bandung City. It is done by testing the indicators of subjective well-being (SWB) (perceptions of family, friends' and school climate) as independent variables on cyber-bullying (the dependent variable). The research samples are collected through convenience sampling technique. The participants are high school students living in Bandung City, ranging from 15 to 18 years old (N = 515; 58.1% female and 41.9% male). The indicators of SWB is measured through a measuring instrument from Children's Worlds, while cyber-bullying is measured through a measuring instrument from Patchin and Hinduja. The mean of SWB score is measured with the Children's Worlds Subjective Well-Being Scale 5 items version (CW-SWBS 5). The data are analyzed with linear regression so as to examine the contribution of socio-demographic variables and the indicators of SWB as the protection factors against cyber-bullying. Descriptive statistic with ANOVA is also performed so as to test the significance of the difference in the mean of SWB. The results show that the indicators on the family and friends' relationships are able to protect high school students (teenagers) from being the victims of cyber-bullying. Those indicators are having a good time with family at home (β = -.182; p < .01), parents who are willing to listen and pay attention to their children (β = -.132; p < .05), as well as get along with friends (β = -.158; p < .05). The indicators of socio-demographic show that women have a greater chance of being the victims of cyber-bullying (β = -.108; p < .05). Furtheormore, the mean score of SWB from the students (M= 67.60; SD = 20.98) is lower than the normal mean score of SWB that is based on the criteria of Cummins' homoestatic theory. Abstrak. Penelitian ini bertujuan menginvestigasi faktor protektif perundungan siber pada siswa SMA di Kota Bandung dengan menguji indikator subjective well-being (SWB) sebagai variabel bebas (persepsi terhadap relasi dalam keluarga, relasi dengan teman, dan iklim sekolah) terhadap perundungan siber sebagai variabel terikat. Sampel diambil menggunakan teknik convenience sampling. Partisipan penelitian adalah siswa SMA di Kota Bandung berusia 15-18 tahun (N = 515; 58.1% perempuan dan 41.9% laki-laki). Indikator SWB diukur menggunakan alat ukur persepsi siswa terhadap relasi dalam keluarga, relasi dengan teman, dan iklim sekolah dari Children’s Worlds. Perundungan siber diukur menggunakan alat ukur korban perundungan siber dari Patchin dan Hinduja. Nilai rerata skor SWB diukur menggunakan the Children’s Worlds Subjective Well-Being Scale versi 5 item (CW-SWBS 5). Data dianalisis menggunakan regresi linier untuk menguji kontribusi variabel sosiodemografis dan indikator SWB sebagai faktor proteksi terhadap perundungan siber. Statistika deskriptif menggunakan ANOVA dilakukan untuk menguji signifikansi perbedaan rerata SWB. Hasil penelitian menunjukkan bahwa indikator pada relasi dengan keluarga dan relasi dengan teman memberikan kontribusi dalam memproteksi remaja dari kemungkinan menjadi korban perundungan siber. Indikator tersebut adalah memiliki waktu yang menyenangkan dengan orang di rumah (β = -.182; p < .01), orang tua mendengarkan serta memperhatikan anak (β = -.132; p < .05), serta akur dengan teman (β = -.158; p < .05). Indikator sosiodemografis menunjukkan bahwa perempuan memiliki peluang yang lebih besar untuk menjadi korban perundungan siber (β = -.108; p < .05). Siswa memperlihatkan skor rerata SWB (M= 67.60; SD = 20.98) lebih rendah dibandingkan nilai rata-rata normal SWB berdasarkan kriteria teori homoestatis Cummins.